Philosophical Hermeneutics: A Path to Intercultural Understanding Through Translation - Panahbar, Ehsan; Dabaghi, Azizollah (Richtmann Publishing, 2012)
In philosophical hermeneutics, the thoughts of Gadamer and Ricoeur about conditions of attaining to understandingare of utmost interest. Gadamer, by proposing